Description of the Behavior of Aedes aegypti Mosquito Laying Eggs in Water Contaminated with Animal Feces and Soil - Firda Yanuar Pradani; Rahayu Nirmatul Mutmainah; Sela Marlina (LPPM STIKes Muhammadiyah Ciamis, 2023)
Background & Objective This study aims to determine the egg-laying behaviour of Aedes aegypti in water contaminated with animal waste and soil, count eggs caught in cages, observe and count the number of healthy and damaged eggs, and compare the number of eggs from each water medium. Method This study is descriptive, the data were analyzed using the SPSS application, presented in tabular form, and explained in a narrative manner. Result The results of observations of egg-laying behaviour indicate that water contaminated with animal waste and soil can be a breeding ground for the Aedes aegypti. Conclusion Based on the results of observations of the behaviour of Aedes aegypti in water media contaminated with animal faeces and soil, it shows a distinctive behaviour, that water contaminated with animal faeces and soil is favoured by Aedes aegypti as a place to lay eggs and breed. The total number of eggs caught was 1,716, with the number of healthy eggs ( 1,219) and the number of damaged eggs (497). Differences in the content contained in the water media affected the laying of Aedes aegypti eggs but did not affect the number of healthy or damaged eggs.